Protective effects of N-acetylcysteine against cadmium-induced damage in cultured rat normal liver cells - ODEWUMI, CAROLINE O. (2010)
In this study, the protective effects of N-acetylcysteine (NAC), a precursor of reduced glutathione, were studied by measuring the viability, the levels of antioxidant enzymes, and by analyzing the cell cycle in cadmium (Cd)-treated rat liver cells. The cells were treated with 150 μM CdCl(2) alone or co-treated with 150 μM CdCl(2) and 5 mM NAC (2 h pre-, simultaneous or 2 h post-treatment) for 24 h. The viability of the cells treated with 150 μM CdCl(2) alone decreased to 40.1%, while that of the cells co-treated with 5 mM NAC (pre-, simultaneous and post-treatment) significantly increased to 83.7, 86.2 and 83.7%, respectively in comparison to the control cells (100%). The catalase enzyme level decreased to undetectable level in the cells treated with CdCl(2) alone, while it significantly increased in the co-treated cells (pre-, simultaneous and post-treatment) to 40.1, 34.3 and 13.2%, respectively. In the cells treated with CdCl(2) alone, the glutathione peroxidase enzyme level decreased to 78.3%, while it increased in the co-treated cells (pre-, simultaneous, and post-treatment) to 84.5, 83.3 and 87.9%, respectively. The glutathione reductase enzyme level decreased to 56.1% in the cells treated with cadmium alone, but significantly increased in the cells co treated with NAC (pre-, simultaneous and post-treatment) to 79.5, 78.5 and 78.2%, respectively. Cd caused cell cycle arrest at the S and G2/M phases. The co-treatment with NAC inhibited cell cycle arrest by shifting the cells to the G1 phase. These results clearly show the protective effects of NAC against Cd-induced damage in rat liver cells.